Peningkatan Kesadaran Kesehatan Masyarakat melalui Sosialisasi Pemantauan Kesehatan Mandiri Berbasis Smart Watch di Gunungpati Kota Semarang - Hadi, Syaikhul; Puspita, Rina; Kuspranoto, Abdul Haris; Anzhari, Della Hashfi (Pakis Journal Institute, 2026)
Hypertension is one of the non-communicable diseases with an increasing prevalence in Indonesia and is often not detected early due to the low level of public awareness in conducting regular health monitoring. The use of wearable technology such as smartwatches can serve as an alternative tool for independent health monitoring that is easily accessible to the community. This community service activity aimed to improve public understanding of independent health monitoring using smartwatches and to increase awareness of the importance of blood donation. The activity was conducted in RW VII Gunungpati Village, Semarang City, involving 114 participants from the PKK community group. The methods used included educational socialization, smartwatch usage demonstrations, and evaluation through pretest and posttest to measure changes in participants’ knowledge levels. The results showed a significant increase in participants’ understanding of health monitoring and smartwatch utilization, where the good knowledge category increased from 15.8% in the pretest to 68.4% in the posttest. In addition, participants’ understanding of the role of the Indonesian Red Cross and the importance of blood donation also increased from 18.4% to 73.7%. These findings indicate that wearable technology-based education is effective in improving community health literacy and has the potential to support the development of a Blood Donor Cadre Village program in Gunungpati.